CLCf is an endosomal resident proton/chloride antiporter during salt stress: letter - McKay, Daniel W.; Krebs, Melanie; Wege, Stefanie; Uebele-Pérez, Michelle; Lupanga, Upendo; Schumacher, Karin (Plant physiology, 2025)
Dear Editor,Chloride is an essential micronutrient for plants, which can have beneficial effects when present at macronutrient levels while excess chloride, as found in saline soils, often has negative impact on plant biomass and especially crop yield (Wege et al. 2017). A reduction of shoot chloride content often positively associates with increased salt stress tolerance and biomass production, particularly a reduction in foliar chloride content (Wu and Li 2019). Shoot chloride content can be regulated by restricting chloride translocation through the root vasculature, for example, by excluding chloride from root epidermal and cortex cells. Chloride that has entered root cells might therefore be exported out of the cell through a plasma membrane (PM) localized chloride selective export protein to regulate chloride content in plants. Different protein families in plants can mediate chloride transport, among them are members of the Chloride Channel (CLC) family. CLC proteins, however, typically localize in endomembrane compartments and not the PM where they could directly mediate chloride export. Chloride transport proteins are crucial in endomembrane compartments as, in addition to the role of chloride in the oxygen evolving complex, stomatal aperture regulation, and turgor-driven cell expansion, chloride is utilized as a countercharge in cellular compartments (Wege et al. 2017). As such, chloride plays a major role in compartments such as the trans-Golgi Network/Early Endosome (TGN/EE), an important trafficking hub in plant cells. The transport circuits and regulation that enable chloride to play this role, however, are not yet fully elucidated. In total, Arabidopsis (Arabidopsis thaliana) has 7 CLCs. CLCa, CLCb, CLCc, and CLCg are found at the tonoplast, CLCd and CLCf in the TGN/EE and CLCe at the thylakoid membrane (De Angeli et al. 2006; Marmagne et al. 2007; von der Fecht-Bartenbach et al. 2007; Jossier et al. 2010; von der Fecht-Bartenbach et al. 2010; Nguyen et al. 2016). CLCd and CLCf are both ubiquitously expressed and appear to compensate the others function, yet, CLCd and CLCf belong to different subgroups of the CLC family and did not arise from a duplication event (Scholl et al. 2021). Therefore, these proteins either evolved to perform redundant roles in plants or these proteins have nonredundant roles that are yet to be identified. Double knockouts are not viable even under standard, nonstressed conditions (von der Fecht-Bartenbach et al. 2007; Scholl et al. 2021).